Innovative Principal Leadership in Managing an Effective Learning Environment: A Case Study of SD Inpres 2 Besusu - Nur Fina; Juraid Abdul Latief; Rizal Rizal; Nashrullah Nashrullah; Mas'adi Mas'adi (Journal of Educational Sciences, 2026)
This study aims to describe the innovative leadership of the principal in managing an effective learning environment at SD Inpres 2 Besusu. The study employed a qualitative approach using a descriptive method. The research subjects consisted of the principal, teachers, and educational staff. Data collection techniques were conducted through observation, semi structured interviews, questionnaires, and documentation, while data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the principal’s innovative leadership contributes very positively to the creation of an effective learning environment, as reflected in teachers’ high perceptions of the principal’s leadership and learning environment management. Interview findings revealed that the principal was able to encourage teachers’ creativity, support the use of educational technology, build harmonious social relationships, and create a safe, comfortable, and conducive learning atmosphere. The innovations implemented included the development of digital based learning, the organization of training sessions and workshops, as well as improvements to the school’s physical environment to support learning comfort. These findings indicate that the principal’s innovative leadership plays an important role in improving the effectiveness of the learning environment through strengthening teacher motivation, student engagement, and the quality of the learning process in elementary schools.